Bismuth nanosheets Q-switched Nd:BGO laser operating at 1065 nm with 880 nm laser-diode pumping. (July 2020) - Feng, Xiaoyue; Hao, Qianqian; Lin, Yunkun; Yu, Xiuru; Wu, Qinghui; Huang, Hao; Zhang, Feng; Liu, Jie; Su, Liangbi; Zhang, Han
Highlights: Continuous-wave Nd:BGO laser was first obtained with 880 nm laser-diode pumping. Passive Q-switching was first achieved by the Bismuth nanosheets absorber at 1 μm. The results show a high-efficiency, beam quality, and repetition-rate Nd:BGO laser. Abstract: We report a passively Q-switched Nd:BGO laser at 1065 nm based on a Bismuth nanosheets saturable absorber. The Nd:BGO crystal was successfully grown by the micro-pulling-down method, and first obtained the continuous-wave laser operation with 880 nm laser-diode pumping. Moreover, for the first time, the passive Q-switching was achieved by the Bismuth nanosheets absorber at 1 μm. Under the absorbed pump power of 3.3 W, the shortest pulse width and maximum repetition rate were 256 ns and 223.7 kHz, respectively. The maximum single pulse energy was 0.59 μJ and the corresponding peak power was 1.55 W. The results demonstrate that the 880 nm diode directly-pumped Q-switched Nd:BGO laser can generate high-efficiency, high-beam-quality, and high-repetition-rate all-solid-state lasers.